Epilepsy Towards the Next Decade New Trends and Hopes in Epileptology - Striano, Pasquale (Contemporary Clinical Neuroscience,, 2015)
A comprehensive collection of the most recent knowledge on the biological bases of various kinds of epilepsies and modern clinical approaches to their treatment. Epilepsy affects about 0.5-1% of the world's population (about 50,000,000 individuals) and the main goal of its treatment is to eliminate seizures without creating side effects.       Despite numerous advances in the treatment of epilepsy and the approval of several new antiepileptic drugs, about 30% of patients continue to experience recurrent seizures which are medically, physically, and/or socially disabling. The editor of this volume hopes that by bridging the gap between the fundamental biology of epilepsy and its clinical implications he might spur further research and treatment options.